2011
DOI: 10.1002/pds.2211
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant use of anti‐dementia drugs with psychotropic drugs in Norway—a population‐based study

Abstract: The concomitant use of psychotropic drugs with anti-dementia drugs was extensive, especially among women. Co-medication with potentially interacting drugs occurred at a rate of one in 10. The concomitant use of anti-dementia drugs with psychotropic drugs identified in this study may inform the ongoing clinical debate about drug use in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Regarding the co-prescription rate, an earlier Japanese study reported that more than 20% of people living with dementia used donepezil concomitantly with psychotropic drugs, 40 and a Norwegian study showed that 60% of all dementia patients using anti-dementia drugs were prescribed psychotropic drugs. 41 We found a co-prescription rate of 24.1%, which is similar to the Japanese study but much lower than the Norwegian study. Given the potential side effects of psychotropic drugs and the concomitant prescription of psychotropic and anti-dementia drugs, the Chinese dementia guidelines recommend that polypharmacy should largely be avoided, and the trade-off between treating neuropsychiatric symptoms and decreasing side effects should be considered cautiously.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding the co-prescription rate, an earlier Japanese study reported that more than 20% of people living with dementia used donepezil concomitantly with psychotropic drugs, 40 and a Norwegian study showed that 60% of all dementia patients using anti-dementia drugs were prescribed psychotropic drugs. 41 We found a co-prescription rate of 24.1%, which is similar to the Japanese study but much lower than the Norwegian study. Given the potential side effects of psychotropic drugs and the concomitant prescription of psychotropic and anti-dementia drugs, the Chinese dementia guidelines recommend that polypharmacy should largely be avoided, and the trade-off between treating neuropsychiatric symptoms and decreasing side effects should be considered cautiously.…”
Section: Discussionsupporting
confidence: 75%
“…28 Further, this activity would be likely to negate the effects of the cholinesterase inhibitors in the 25% of patients prescribed both an antipsychotic and a cholinesterase inhibitor. Such co-prescribing has been seen in other large samples of people with dementia, 29 although the efficacy and tolerability of such regimens have not been formally tested in randomised controlled trials.…”
Section: Other Drugs Prescribedmentioning
confidence: 99%
“…Concomitant use of antipsychotics with antidementia drugs was about 16% for both male and female patients. Of the total sample, 11.9% of the women and 11.7% of the men used acetyl cholinesterase inhibitor (AChEI) antidementia drugs concomitantly with an interacting psychotropic drug [22]. …”
Section: Discussionmentioning
confidence: 99%